Simulation of wideband inverted suspended patch antenna - Rahayu, Yusnita; Ngah, Razali; Abd. Rahman, Tharek (2005)
The radio spectrum is finite, but bandwidth utilization for wireless communication is increasing exponentially due to the emergence of new standards driven by the rapid growth in information services provided by the Internet. Therefore, there is a need for new technology that can open a new door to wireless communication. Ultra wide band (UWB) technology based on the use of very narrow pulses on the order of nanoseconds, covering a very wide bandwidth in the frequency domain, could be a possible solution to this problem. UWB has had a substantial effect on antenna design. This paper presents a wide band inverted suspended patch antenna design for UWB applications. The designed antenna is simulated using advanced design system (ADS). For initial result, this antenna obtains 5 GHz of bandwidth at frequency 4.5 GHz to 9.5 GHz with maximum VSWR of 2.